Complete chloroplast genome sequences of Phlomis fruticosa and Phlomoides strigosa and comparative analysis of the genus Phlomis sensu lato (Lamiaceae) - Zhao, Wei; Guo, Lirong; Yang, Yu; Wang, Yan; Yang, Li; Wei, Cuimei; Guo, Jian; Yan, Kan; Chen, Haijuan; Yang, Zhigang; Li, Yimeng (Frontiers in Plant Science, 2022)
Phlomis (Lamiaceae: Lamioideae) is a contentious genus, in which “Phlomis” and “Phlomoides” are argued as two sections within Phlomis s.l., or as two independent genera. Recent phylogenetic analyses using molecular markers showed that Phlomis and Phlomoides formed two monophyletic clades, and thus they were claimed as separate genera. However, due to the low resolution of phylogenetic results based on molecular markers of low variation, stronger quantitative evidence is necessary to examine this demonstration. In this study, we assembled the complete chloroplast genome of Phlomis fruticosa, which is the first reported chloroplast genome belonging to Phlomis s.str. (or sect. Phlomis), as well as Phlomoides strigosa belonging to Phlomoides s.str. (or sect. Phlomoides). The results showed that the length of chloroplast genome was 151,639 bp (P. fruticosa) and 152,432 bp (P. strigosa), with conserved large single copy regions, small single copy regions, and inverted repeat regions. 131 genes in P. fruticosa and 133 genes in P. strigosa were annotated. The chloroplast genomes of P. fruticosa, P. strigosa, and three reported Phlomis species, as well as seven species from Leonurus, Lagopsis, Paraphlomis, and Stachys (Lamiaceae) were subjected to the phylogenetic analysis. The Phlomis and Phlomoides species were split into two groups, which was consistent with previous analyses using molecular markers. Notably, the evolutionary distance between P. fruticosa and the Phlomoides group was even longer than that between P. fruticosa and Leonurus genus, suggesting that the diversity between the Phlomis and Phlomoides was in the generic level. Our study provided strong evidence to recognize Phlomis and Phlomoides as independent genera.